Regulation of Autonomic Motility in Human Gastric Muscle and the Gastroepiploic Artery by Stretch and pH - Dae Hoon Kim; Seung Myoung Son; Woong Choi; Chan Hyung Kim; Hun Sik Kim; Ki Bae Kim; Wen-Xie Xu; Sang Jin Lee; Young Chul Kim; Hyo-Yung Yun (Journal of Muscle Research and Cell Motility, 2025)

CBT-Cys click ligation coupled with pregnancy test strips for nucleic acid assay - Meiling Zhang; Jiahang Song; Huawen Zhang; Yang Li; Xu Hun (Analytica Chimica Acta, 2025)

CO2 enrichment enhances biomass density and C:N:P ratios in phytoplankton assemblage in the coastal water of the Taiwan Strait - Yumeng Pan; Xiang Yang; Jinlong Shang; Xi Liu; Yinrui Wang; Junqin Cai; Yubin Hu; Kui Xu; Zhengke Li; Yonghe Han; Hong Zhang; Hun Xue; et al. (Journal of Applied Phycology, 2025)

Highly activated phosphate-derived oxyhydroxide overlayer for enhancing photoelectrochemical ammonia oxidation-boosted hydrogen evolution - Phuong Thi Pham; Jong Hun Kim; Won Tae Hong; Hyungu Han; Seung Hun Roh; Xu Yu; Heeyeop Chae; Jongwook Park; Min-Cheol Kim; Chang Hyuck Choi; Jung Kyu Kim (Chemical Engineering Journal, 2025)

Approaching high rate All-Solid-State Lithium-Sulfur batteries via promoted sulfur conversion with nickel oxide nanoparticle electrocatalyst - Seok Hun Kang; Won-Gwang Lim; Liangliang Xu; Donghyeok Son; Young-Gi Lee; Jinwoo Lee (Chemical Engineering Journal, 2024)

PKHD1L1, a gene involved in the stereocilia coat, causes autosomal recessive nonsyndromic hearing loss - Shelby E. Redfield; Pedro De-la-Torre; Mina Zamani; Hanjun Wang; Hina Khan; Tyler Morris; Gholamreza Shariati; Majid Karimi; Margaret A. Kenna; Go Hun Seo; Hongen Xu; Wei Lu; et al. (Human Genetics, 2024)
Identification of genes associated with nonsyndromic hearing loss is a crucial endeavor given the substantial number of individuals who remain without a diagnosis after even the most advanced genetic testing. PKHD1L1 was established as necessary for the formation of the cochlear hair-cell stereociliary coat and causes hearing loss in mice and zebrafish when mutated. We sought to determine if biallelic variants in PKHD1L1 also cause hearing loss in humans. Exome sequencing was performed on DNA of four families segregating autosomal recessive nonsyndromic sensorineural hearing loss. Compound heterozygous p.[(Gly129Ser)];p.[(Gly1314Val)] and p.[(Gly605Arg)];p[(Leu2818TyrfsTer5)], homozygous missense p.(His2479Gln) and nonsense p.(Arg3381Ter) variants were identified in PKHD1L1 that were predicted to be damaging using in silico pathogenicity prediction methods. In vitro functional analysis of two missense variants was performed using purified recombinant PKHD1L1 protein fragments. We then evaluated protein thermodynamic stability with and without the missense variants found in one of the families and performed a minigene splicing assay for another variant. In silico molecular modeling using AlphaFold2 and protein sequence alignment analysis were carried out to further explore potential variant effects on structure. In vitro functional assessment indicated that both engineered PKHD1L1 p.(Gly129Ser) and p.(Gly1314Val) mutant constructs significantly reduced the folding and structural stabilities of the expressed protein fragments, providing further evidence to support pathogenicity of these variants. Minigene assay of the c.1813G>A p.(Gly605Arg) variant, located at the boundary of exon 17, revealed exon skipping leading to an in-frame deletion of 48 amino acids. In silico molecular modeling exposed key structural features that might suggest PKHD1L1 protein destabilization. Multiple lines of evidence collectively associate PKHD1L1 with nonsyndromic mild–moderate to severe sensorineural hearing loss. PKHD1L1 testing in individuals with mild–moderate hearing loss may identify further affected families.

Improved tolerance capacity and expression of degradation genes drive efficient removal of sulfamethizole by Chlorella pyrenoidosa - Ying Liang; Xin Qi; Jia-Min Xu; Mayur B. Kurade; Byong-Hun Jeon; Li-Qiang Yang; Jiu-Qiang Xiong (Journal of Environmental Chemical Engineering, 2024)

CRISPR/Cas12a-based MUSCA-PEC strategy for HSV-1 assay - Bohao Dou; Yinhao Zhang; Huiyu Gao; Shenghao Zhang; Jie Zheng; Xu Lu; Shishi Liu; Hong Zhou; Xu Hun (Analytica Chimica Acta, 2023)

Modern pollen and land-use relationships in the Taihang mountains, Hebei province, northern China—a first step towards quantitative reconstruction of human-induced land cover changes - Jianyong Li; Qinghai Xu; Marie-José Gaillard-Lemdahl; Heikki Seppä; Yuecong Li; Lingyun Hun; Manyue Li (Vegetation History and Archaeobotany, 2013)

The Zanthoxylum schinifolium seed oil modulates immune function under the biological safety level - Joung-Wook Seo; Dae-Hun Park; Yong-Chun Li; Hur-Je Kang; Hong De Xu; Young-Jin Kim; Jong-Hwa Lee; Myung-Sup Lee; In Chul Lee; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; et al. (Molecular & Cellular Toxicology, 2012)

Biological safety and B cells activation effects of Zanthoxylum schinifolium - Dae-Hun Park; Yong-Il Park; Yong-Chun Li; Hong De Xu; Jong-Hwa Lee; Young-Jin Kim; Soon-Ae Jang; Sung Jin Park; Yun Lyul Lee; Jae-Bum Ahn; Soon-Chang Cho; Min-Jae Lee (Molecular & Cellular Toxicology, 2011)

Rapid Variability in the Japan/East Sea: Basin Oscillations, Internal Tides, and Near-Inertial Oscillations - Jae-Hun Park; D. Randolph Watts; Mark Wimbush; Jeffrey Book; Karen Tracey; Yongsheng Xu (Oceanography, 2006)